PENGARUH BRAND IMAGE PELANGGAN TELKOMSEL TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus: Mahasiswa Fakultas Ekonomi Unika Santo Thomas SU) - Sitepu, Silvia R.; Tamba, Darwis (UNIKA Santo Thomas, 2013)
The purpose of research to determine the effect of brand image components consisting of image makers, user image and product image provider Telkomsel customers on purchasing decisions and to determine the components of the brand image is the image makers, user image and product image provider Telkomsel subscribers Which has more influence on purchasing decision. The population of this study were all students of the Faculty of Economics, University of St. Thomas Catholic North Sumatra. Samples were taken 96 people. Data collection techniques used by questionnaire and data analysis technique used is multiple linear regression equation. Based on the results of research and discussion shows that the component brand image consisting of a variable image-makers, the user's image and product image provider Telkomsel subscribers simultaneously significant effect on consumer purchasing decisions. Partially indicates that the component brand image consisting of a variable image-makers, the user's image and product image provider Telkomsel subscribers partially significant effect on purchasing decisions students of the Faculty of Economics, University of St. Thomas Catholic North Sumatra.